Ketika Istri Lebih Layak Memimpin: Menilai Kembali Peran Rumah Tangga: (Telaah terhadap Hukum Islam, UU Perkawinan, dan KHI) - Roidatus Shofiyah (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze the relevance of the wife's role as head of household amidst the social and economic changes in modern Indonesian society. Using a descriptive quantitative approach based on secondary data from Statistics Indonesia (BPS) and legal sources, the research reveals a significant increase in women’s participation in the workforce and higher education. These findings suggest the need to reconsider traditional household roles as outlined in Law No. 1 of 1974 and the Compilation of Islamic Law (KHI).